Penentuan Kerapatan Massa Tajuk Pohon Decurrent Berdasarkan Analisis Keragaan Fisik - Aini, Siti Churotul; Ulfa Adzkia; Agus Buono; Siregar, Iskandar Zulkarnaen; Lina Karlinasari (Universitas Gadjah Mada, 2026)
Self-weight calculation was identified as an essential step in tree structural analysis. In practice, this calculation included estimating stem weight based on wood density, while crown density was expressed as a percentage of crown area. However, previous research had not provided explicit methodologies for determining crown density as a function of crown mass and volume. Therefore, this research aimed to establish a proper method and corresponding conversion factors for translating area-based crown density estimates to those derived from crown weight and volume. A total of 15 healthy decurrent trees were selected to assess crown volume and density through physical attribute analysis. The new crown area density was calculated after pruning, where all pruned crown biomass was collected and weighed to determine crown mass. Mathematical analyses were developed to convert crown density values. The results showed that decurrent trees had a mean crown density of approximately 2.95 kg/m3, exceeding the value reported in reference research for excurrent trees (1.9 kg/m3). Since this research focused on tropical tree species, the results could serve as a reference for subsequent research on tropical tree structural characteristics.